ILLUSTRATION DESIGN OF ICONIC BUILDING OF SEMARANG APPLIED ON MERCHANDISE - Abdul Gani, Aqil; Haryanto, Eko (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2021)
Semarang is one of the cities that has the potential for iconic building tourism. With the various kinds of iconic buildings in Semarang, it’s necessary to have promotional media that supports to disseminate tourism information on iconic buildings in Semarang, which is merchandise media. All merchandise designs that are made contain visual illustration designs with realist illustrative depictions of the surreal approach of the iconic buildings in Semarang. The design process starts from manual manufacturing of illustrations. The illustration design is made using manual techniques and digital finishing through the Adobe Photoshop CC 2019 software. The process of produce merchandise design through several stages of the pre-production process, the production process, the post-production process. The product are t-shirts, tote bags, key chains, wall hangings, flower pots, pillows, soft case, masks, binders, mugs and plates, and decorative lamps. Through the design of this merchandise , it’s hoped that it can increase the number of tourist visits, and can provide broad information to the public about what iconic buildings are in Semarang.